Upaya Meningkatkan Hasil Belajar IPS Dengan Model Pembelajaran Kooperatif Tipe STAD Pada Kelas IV MI Terpadu Al Muttaqin Sawangan - Azizah, Anisa Nur (Prosiding University Research Colloquium, 2021)
This study aims to improve social studies learning outcomes by using the STAD type cooperative learning model for the fourth grade students of MI Terpadu Al Muttaqin, Sawangan District, Magelang Regency. The research subjects were 4th grade students of the Integrated MI Al Muttaqin, Sawangan District, Magelang Regency which consisted of 14 boys and 4 girls. Data collection techniques are documentation, observation, and tests. The analytical technique used is comparative descriptive. The results showed that the STAD model could improve the social studies learning outcomes of the 4th grade students of MI Terpadu Al Muttaqin Sawangan District, Magelang Regency. an increase in cycle 1 to 89% of students who completed, then in cycle 2 it increased to 94%. Learning with the STAD type cooperative model needs to be implemented in social studies learning in the classroom, because the learning model can improve student learning outcomes. Teachers must be able to motivate students to be more active in learning by conducting intensive guidance.